Effectiveness of Adjunctive Reboxetine on Deficit Symptoms of Schizophrenia - Shafti , Saeed Shoja (International Journal of Psychosocial Rehabilitation, 2014)
Objective: Deficit syndrome is an important dilemma against social participation of schizophrenic patients. Reboxetine is a norepinephrine reuptake inhibitor (NRI) .Objective of this study was to evaluate its effect on the negative symptoms of schizophrenia.Method: in a 12-week randomized placebo-controlled trial, reboxetine was compared with placebo, as an ad- junctive to haloperidol (5 mg), for treatment of 50 patients meeting DSM-IV-TR criteria for schizophrenia. In this respect, Scale for Assessment of Negative Symptoms (SANS) was used as the primary outcome measure. Treatment efficacy was analyzed by t test, Split-plot (Mixed) and repeated –measures analysis of variance (ANOVA).Result: The primary finding of this trial was a significant reduction in mean total scores of SANS in the re- boxetine group, in comparison with the placebo group, at the end of the 12th week (P